The nonlinear association between the triglyceride glucose-waist-to-height ratio index and cardiovascular disease among middle-aged and older adults in China with cardiovascular-kidney-metabolic syndrome stages 0–3 - Huang, Cheng; Jia, Jing; He, Yuanyuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease (CVD) poses a critical challenge to global public health, especially in individuals with Cardiovascular-Kidney-Metabolic (CKM) syndrome. The association between the triglyceride glucose-waist-to-height ratio index (TyG-WHtR) and CVD among middle-aged and older Chinese adults with CKM stages 0–3 is not well understood.MethodsData were obtained from the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative longitudinal study of individuals aged 45 years and older. Cox proportional hazards models were constructed to evaluate the association between TyG-WHtR and CVD risk. Subgroup analyses were conducted among different groups to evaluate consistency of findings and explore potential interactions. Restricted cubic spline regression was employed to evaluate the dose-response relationship.ResultsDuring a mean follow-up period of 7.77 ± 2.13 years, 1,595 participants (23.58%) developed CVD. After adjusting for covariates, TyG-WHtR was significantly associated with CVD risk (HR: 1.09, 95% CI: 1.01–1.18). Notably, this relationship was independent of other variables and displayed a nonlinear pattern, with an inflection point identified at 3.57. Beyond this threshold, the adjusted HR increased to 1.17 (95%CI: 1.08–1.71).ConclusionTyG-WHtR demonstrates a nonlinear relationship with CVD among middle-aged and older Chinese adults with CKM stages 0–3.